2021
DOI: 10.21608/jvmr.2021.55209.1027
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the bactericidal effect of silver nanoparticles against Methicillin Resistant Staphylococcus aureus (MRSA) and Methicillin Sensitive Staphylococcus aureus (MSSA) strains isolated from mastitic milk of small ruminants and their surrounding environment in Aswan

Abstract: In the recent years, emergence of infectious diseases caused by drug resistant pathogens had been increased; therefore there is an urgent need to search for new alternative and effective antimicrobial agents to overcome the drug resistance. In the present investigation, the study group consisted of 90 sheep and 90 goats with clinical evidences of mastitis in 17(18.89%) goats and 5 sheep (5.56%) that manifested swollen udder with or without systemic signs of illness related to mastitis. Standard bacteriology wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…On analysis of S. aureus sensitivity showed resistance to penicillin G and methicillin was 100% and this result is in agreement with [48][49][50]. S. aureus resistance to β-lactam antibiotics is due to mecA gene, which encodes a modifed penicillin binding protein that confers resistance to methicillin and other penicillin derivatives carried on a mobile gene element called the "staphylococcal cassette-…”
Section: Discussionsupporting
confidence: 70%
“…On analysis of S. aureus sensitivity showed resistance to penicillin G and methicillin was 100% and this result is in agreement with [48][49][50]. S. aureus resistance to β-lactam antibiotics is due to mecA gene, which encodes a modifed penicillin binding protein that confers resistance to methicillin and other penicillin derivatives carried on a mobile gene element called the "staphylococcal cassette-…”
Section: Discussionsupporting
confidence: 70%
“…In microbiology, nanotechnology provides effective solutions to combat biofilms and their related infections by employing drug-loaded NPs [ 101 ]. The nano-sized particles exhibit a relatively greater surface area, representing an advantage to penetrate the cell membrane and undermine the viability of bacterial pathogens [ 102 ]. Indeed, knowledge regarding nanomaterials’ characteristics, mechanism, and transport are essential criteria for designing appropriate NPs with antimicrobial potency [ 103 ].…”
Section: Nanotechnology-based Approaches To Target Staphylo...mentioning
confidence: 99%
“…Additionally, using NPs (nanoparticles) offers a solid policy to cope with infections and diseases triggered by MDR bacteria in animals (Farouk et al, 2020;Salah et al, 2020;Abdalhamed et al, 2021a;Masimen et al, 2022). Salah et al (2020) reported AgNPs exhibited a robust bactericidal influence against S. aureus isolated from mastitic ewes and goats.…”
mentioning
confidence: 99%
“…Additionally, using NPs (nanoparticles) offers a solid policy to cope with infections and diseases triggered by MDR bacteria in animals (Farouk et al, 2020;Salah et al, 2020;Abdalhamed et al, 2021a;Masimen et al, 2022). Salah et al (2020) reported AgNPs exhibited a robust bactericidal influence against S. aureus isolated from mastitic ewes and goats. In investigations on small ruminants, Farouk et al (2020) clarified the influential capacity of AgNPs to combat MDR Salmonella spp., according to the in vivo and in vitro trials without adversative impacts.…”
mentioning
confidence: 99%